FOSSILS - Romero, Libby; Smith, Grace Hill; Myers, Maya; Weglinski, Michaela (London : Penguin Random House, 2023)
Use your reading superpowers to learn all about different fossils and what they tell us about life millions of years ago - a high-quality, fun, nonfiction reader - carefully leveled to help children progress.
Includes index
Includes questions and exercises
Keywords: Paleontology -- Juvenile literature; Fossils -- Juvenile literature; Readers (elementary)